EtherYou: Ethereum-based privacy-preserving social media platform - Oyama, Pedro Ivo de Castro; Ueyama, Jó; Matias, Paulo (Workshop em Blockchain: Teoria, Tecnologias e Aplicações (WBlockchain); 2020: Anais do III Workshop em Blockchain: Teoria, Tecnologia e AplicaçõesDO - 10.5753/wblockchain.2020.12439, 2020)
Social media has become part of our daily lives. It brought significant developments in the way we communicate, but it also raised some concerns, including privacy and censorship. In this context, this work presents a social media platform -- EtherYou -- that makes use of cryptographic primitives and an Ethereum smart contract to overcome these issues. Experiments were conducted to evaluate the operating costs involved. The results showed considerable values for senders, zero for receivers, and zero maintenance costs, indicating its potential in scenarios with a reduced number of content producers and a large number of consumers. The proposal offers users privacy over their data, transparency on the system behaviour and censorship resistance.